2015
DOI: 10.1186/s12937-015-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined ginger extract & Gelam honey modulate Ras/ERK and PI3K/AKT pathway genes in colon cancer HT29 cells

Abstract: BackgroundThe interconnected Ras/ERK and PI3K/AKT pathways play a central role in colorectal tumorigenesis, and they are targets for elucidating mechanisms involved in attempts to induce colon cancer cell death. Both ginger (Zingiber officinale) and honey have been shown to exhibit anti-tumor and anti-inflammation properties against many types of cancer, including colorectal cancer. However, there are currently no reports showing the combined effect of these two dietary compounds in cancer growth inhibition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 43 publications
8
53
2
Order By: Relevance
“…In numerous malignant tumor types, including breast cancer and non-small cell lung cancer, the PI3K/Akt signaling pathway may prevent the death of cancer cells from chemotherapy or radiotherapy-induced apoptosis (12). Selectively inhibiting PI3K or Akt activity to decrease the phosphorylation of Akt may increase the sensitivity of cells towards apoptosis induced by chemotherapy and radiotherapy (23). For lymphoma with high expression levels of Akt, mTOR inhibitors significantly increase the chemotherapy-induced apoptosis rate of cancer cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous malignant tumor types, including breast cancer and non-small cell lung cancer, the PI3K/Akt signaling pathway may prevent the death of cancer cells from chemotherapy or radiotherapy-induced apoptosis (12). Selectively inhibiting PI3K or Akt activity to decrease the phosphorylation of Akt may increase the sensitivity of cells towards apoptosis induced by chemotherapy and radiotherapy (23). For lymphoma with high expression levels of Akt, mTOR inhibitors significantly increase the chemotherapy-induced apoptosis rate of cancer cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another research done by a researcher called Hakim T. also supports what Tahir did conclude in his research but he found that GH enhances anti-cancer effect of 5-FU (5-flurouracill) against colorectal cancers (13,14).…”
Section: Introductionmentioning
confidence: 48%
“…Tahir T. and his colleagues examined the GH on colon cancer cells and they conclude that it may be an effective chemo-preventive and therapeutic strategy for inducing death to colon cancer cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ng et al [46] looked at the potential effects of Piper betle leaf extract to reduce the 5-Fluorouracil dosage required to exert the same cytotoxicity in HT29 and HCT116 cells. Tahir et al [48] studied the combined effects of Zingiber officinale extracts and Gelam honey on viability of HT29 cells. Some researchers have also studied the potential mechanism of the selected species beyond cytotoxicity tests.…”
Section: Ht29 and Ccd-18comentioning
confidence: 99%